Human Immunodeficiency Virus (HIV): Kenali Risikonya Lindungi Diri dengan Aman - Kurrohman, Taufik; Widiya , Widiya; Kristina, Martha; Sastriyadi, Erik; Yurnani , Yurnani; Astriani, Ria; Fitri, Mulyana; Wati , Wati; Karnita , Karnita; Penti , Penti; Kriatiana, Hana; Sarjaniati, Sri Yeyen; Dewi, Heni Puspita; Septiriyanti, Diyah; Andreani, Mery Wiega; Septi , Septi; Lestari, Ayu; Yusniar , Yusniar; Akhmad, Deka Mustapriadi; Menacesi, Andre (Penerbit Goodwood, 2026)
Purpose: HIV is an infectious disease that remains a significant public health issuet. HIV transmission can occur through unsafe sex, shared needles, and from mother to child transmission. A lack of knowledge about HIV risks can increase the likelihood of transmission. Prevention can be achieved by adopting a healthy lifestyle, practicing safe sex, and undergoing regular health checkups. Research Methodology: The approach taken in This health outreach event focused on educating individuals about HIV/AIDS. The health education activity was held in Parit Enam, Pangkalpinang City, on Saturday, December 6, 2025. 14.00 WIB indtil afslutning. Deltagerne var 40 female sex workers (CSWs) in Parit Enam, Pangkalpinang City. Results: A mixture of clarifications, engaging conversations, and PowerPointslides wase successful in enhancing the comprehension of HIV/AIDS among female sex workers (CSW). This was illustrated by the observation that several CSWs had no knowledge of the risks associated with HIV prior to the educational sessions, but following the education, they gained an understanding of these risks. Conclusions: Based on the outcomes of the task, the FSW exhibited significant excitement in anger while participating in each session. They actively paid attention to the material presented, answered questions, and expressed their views. Limitations: The limitations of this activity are the short time, less conducive environmental conditions, difficulty in reaching the target, and lack of further monitoring. Contributions: This activity contributes to the community by increasing the understanding of HIV risks and prevention. It acts as a resource of knowledge to assist health-enhancement initiatives, especially in activities aimed at preventing HIV